De eerste bezoekers in het nieuwe gebouw aan de Cruquiusweg worden verwelkomd door mej. Tijssen (midden)
De eerste bezoekers in het nieuwe gebouw aan de Cruquiusweg worden verwelkomd door mej. Tijssen (midden).